Antibacterial Activity Test Of Ethanol Extract Of Matoa Leaves (Pometia pinnata) Against Bacteria That Cause Digestive Tract Infections - Kamilah, Eva (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Matoa Leaves (Pometia Pinnata) Are One Of The Plants That Are Effective As An Antibacterial. This Study Aims To Determine The Antibacterial Activity Of Ethanol Extract Of Matoa (Pometia Pinnata) Leaves Against Several Bacteria That Cause Digestive Tract Infections. This Research Method Was Carried Out Experimentally To Test The Antibacterial Activity Of Matoa (Pometia Pinnata) Leaves Using An Antibacterial Screening Test, MIC Test And KBM Test With Varying Concentrations Of 0.05%, 0.1%, 0.2%, 0.4%, 0.8%, 1.6%, 3.2%, And 6.4%. As Well As Antibacterial Activity Tests With Varying Concentrations Of 1.6%, 3.2% And 6.4%. The Results Obtained In The Screening Test With A Concentration Of 0.1% Showed No Growth In All The Test Bacteria Used, For The MIC Values, Namely Eschericia Coli 0.2%, Salmonella Typhi 0.8%, And Vibrio Cholerae 0.4%, For The KBM Values Eschericia Coli 0.4%, Salmonella Typhi 1.6%, And Vibrio Cholerae 0.8%. As Well As The Results Of Antibacterial Activity Testing, The Largest Inhibitory Zone Diameter Was Obtained For Escherichia Coli Bacteria At A Concentration Of 4.8%, Namely (18.26mm), For Salmonella Typhi Bacteria At A Concentration Of 4.8%, Namely (15.36mm), And For Vibrio Cholerae Bacteria At A Concentration Of 4.8 % Which Is (15.74mm). The Ethanol Extract Of Matoa (Pometia Pinnata) Leaves Has Antibacterial Activity